2018
DOI: 10.1002/anie.201806732
|View full text |Cite
|
Sign up to set email alerts
|

Robust Ultramicroporous Metal–Organic Frameworks with Benchmark Affinity for Acetylene

Abstract: Highly selective separation and/or purification of acetylene from various gas mixtures is a relevant and difficult challenge that currently requires costly and energy-intensive chemisorption processes. Two ultramicroporous metal-organic framework physisorbents, NKMOF-1-M (M=Cu or Ni), offer high hydrolytic stability and benchmark selectivity towards acetylene versus several gases at ambient temperature. The performance of NKMOF-1-M is attributed to their exceptional acetylene binding affinity as revealed by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
358
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 407 publications
(385 citation statements)
references
References 37 publications
23
358
4
Order By: Relevance
“…As shown in Figure a–c, all M‐gallates exhibited perpendicular C 2 H 2 uptake (80.4, 98.4, 87.1 cm 3 g −1 for Ni‐, Mg‐, Co‐gallate, respectively) at 298 K and 1.0 bar. The capacities of C 2 H 2 at 298 K and 1.0 bar of M‐gallate, for example, Ni‐gallate (80.4 cm 3 g −1 ), compared with UTSA‐200 (81.9 cm 3 g −1 ), SIFSIX‐2‐Cu‐i (90.0 cm 3 g −1 ), M′MOF‐3 (42.6 cm 3 g −1 ), UTSA‐100 (88.6 cm 3 g −1 ), NKMOF‐1‐Ni (61.0 cm 3 g −1 ), and NKMOF‐1‐Cu (51.0 cm 3 g −1 ) showed an excellent capacity and predictable selective capturing of C 2 H 2 over C 2 H 4 . After careful comparison, it could be found that the slight enlargement of the pore sizes (≈0.3 Å) from Co‐gallate to Ni‐gallate also enabled higher C 2 H 2 uptakes at low pressure within 0.05 bar (Figure d), that is, 59.6 cm 3 g −1 , 70.6 cm 3 g −1 , and 69.9 cm 3 g −1 for Ni‐, Mg‐, and Co‐gallate materials, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a–c, all M‐gallates exhibited perpendicular C 2 H 2 uptake (80.4, 98.4, 87.1 cm 3 g −1 for Ni‐, Mg‐, Co‐gallate, respectively) at 298 K and 1.0 bar. The capacities of C 2 H 2 at 298 K and 1.0 bar of M‐gallate, for example, Ni‐gallate (80.4 cm 3 g −1 ), compared with UTSA‐200 (81.9 cm 3 g −1 ), SIFSIX‐2‐Cu‐i (90.0 cm 3 g −1 ), M′MOF‐3 (42.6 cm 3 g −1 ), UTSA‐100 (88.6 cm 3 g −1 ), NKMOF‐1‐Ni (61.0 cm 3 g −1 ), and NKMOF‐1‐Cu (51.0 cm 3 g −1 ) showed an excellent capacity and predictable selective capturing of C 2 H 2 over C 2 H 4 . After careful comparison, it could be found that the slight enlargement of the pore sizes (≈0.3 Å) from Co‐gallate to Ni‐gallate also enabled higher C 2 H 2 uptakes at low pressure within 0.05 bar (Figure d), that is, 59.6 cm 3 g −1 , 70.6 cm 3 g −1 , and 69.9 cm 3 g −1 for Ni‐, Mg‐, and Co‐gallate materials, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[8f] However the OMS affinity for both C 2 H 2 and CO 2 is not helpful for C 2 H 2 /CO 2 selectivity.H igh C 2 H 2 /CO 2 -selective MOFs include those with anionic groups such as MF 6 2À (M = Si, Ti,a nd so on) created by Eddaoudi, [2] Zaworotko, [9a] and Chen [9b] because of their strong interactions (such as CH···F) with C 2 H 2 .B ut compared with the best C 2 H 2 -storage MOFs, their uptake capacity is relatively low. [10] Also,t he tailored ultramicropore can endow MOFs with as ieving effect, leading to highly selective adsorption of C 2 H 2 over CO 2 . [11] However,s uch materials usually exhibit much lower C 2 H 2 adsorption capacity owing to low surface area.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of traditional porous materials,s uch as zeolites, [5,6] and activated carbon [7] to separate ternary propyne/propadiene/ propylene gas mixtures has not been realized yet, possibly because of the similar physical properties,s tructure,a nd molecular sizes of propyne,p ropadiene,a nd propylene (Scheme 1). [9][10][11][12][13] Much effort has been devoted to the use of MOFs for the separation of binary gas mixtures, such as acetylene/ethylene, [14][15][16][17][18][19] ethylene/ethane, [14,[20][21][22] carbon dioxide/methane, [23,24] carbon dioxide/nitrogen, [25,26] acetylene/carbon dioxide, [27,28] krypton/xenon, [29] propyne/ propylene, [30,31] and propylene/propane. monotonous structure,l ack of specific binding sites) owing to their welldefined structure,f ine-tunable pore size,a nd customdesigned functional groups.…”
mentioning
confidence: 99%
“…[19] NKMOF-1-M exhibits at hree-dimensional (3D) framework constructed by four-connected [M(pdt) 2 ] À building blocks (Figure 1). [19] NKMOF-1-M exhibits at hree-dimensional (3D) framework constructed by four-connected [M(pdt) 2 ] À building blocks (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation